Tuberculosis and pregnancy. Clinic and treatment - Archard, Arturo (2015)
Through the study done, we draw the following conclusions: that tuberculous pregnant requires joint monitoring tisiólogo and obstetrician, as the only means of study and adequate therapy; in what relates to the influence of pregnancy on tuberculosis it is essential to discover the early lesions, which highlights the importance of antenatal clinics; it is necessary to properly evaluate the influence of pregnancy on tuberculosis, make an exact classification of anatomoclinical forms of the disease, hormonal, metabolic and mechanical influences, which appropriate for prognosis and treatment standards were derived; that with regard to the influence of tuberculosis over the egg, they must be considered various aspects of tuberculosis heritage, and the great value of the son of tuberculous mother; that the problem of the influence of tuberculosis on pregnancy, can express it passes without incident, with the abortion and premature delivery, toxemia direct result of the severe tuberculosis bacilli; that delivery is quick and uneventful, and normal postpartum obstetric point view; the termination of pregnancy as a prophylactic reason of aggravation of tuberculosis pregnant should not arise in the present time for the reasons already stated; the therapeutic to perform in tuberculous pregnant should follow the same guidelines as in non-pregnant, confident of good tolerance of it